Structural dependence on the property of chiral stationary phases derived from chitosan bis(arylcarbamate)-(amide)s. (15th July 2017) - Feng, Zi-Wei; Qiu, Guo-Song; Mei, Xiao-Meng; Liang, Shuang; Yang, Fei; Huang, Shao-Hua; Chen, Wei; Bai, Zheng-Wu
Highlights: Structural dependence on the property of chiral stationary phase (CSP) was studied. A series of the polymers of chitosan bis(arylcarbamate)-(amide)s were synthesized. Methyl-bearing polymers based CSPs showed higher tolerance against eluents. Dichloro-containing polymers based CSPs exhibited lower tolerance towards eluents. CH3 /π bond of the polymers significantly impacts the tolerance of related CSPs. Abstract: The goal of present study was to investigate the structural dependence of chitosan derivatives on enantioseparation and mobile phase tolerance of the corresponding chiral packing materials for liquid chromatography. Hence, a series of chitosan bis(arylcarbamate)-( n -pentyl amide)s and the related chiral stationary phases (CSPs) were prepared from chitosans with different molecular weights. Because of the H-bond formed via CH3 -π interaction, the CSP bearing methyl substituent exhibited high tolerance than the ones bearing dichloro substituents. The CSP derived from the chitosan bis(3, 5-dichlorophenylcarbamate)-( n -pentyl amide) with a higher molecular weight possessed high tolerance to mobile phases, whereas the enantioseparation capability of this CSP was not as good as that of the one prepared from the chitosan derivative with a lower molecular weight. Therefore, enantioseparation capability and mobile phase tolerance have to be counterbalanced in designing chiral selectors for the CSPs derived from chitosan bis(arylcarbamate)-(amide)s.